Cognitive impairment improves the predictive validity of the phenotype of frailty for adverse health outcomes: The Three-City Study. - Avila-Funes JA; Amieva H; Barberger-Gateau P; Le Goff M; Raoux N; Ritchie K; Carrière I; Tavernier B; Tzourio C; Gutiérrez-Robledo LM; Dartigues J (Journal of the American Geriatrics Society, 2009)
OBJECTIVES: To determine whether adding cognitive impairment to frailty improves its predictive validity for adverse health outcomes. DESIGN: Four-year longitudinal study. SETTING: The French Three-City Study. PARTICIPANTS: Six thousand thirty community-dwelling persons aged 65 to 95. MEASUREMENTS: Frailty was defined as having at least three of the following criteria: weight loss, weakness, exhaustion, slowness, and low physical activity. Subjects meeting one or two criteria were prefrail and those meeting none as nonfrail. The lowest quartile in the Mini-Mental State Examination (MMSE) and the Isaacs Set Test (IST) was used to identify subjects with cognitive impairment. The predictive validity of frailty for incident disability, hospitalization, dementia, and death was calculated first for frailty subgroups and then rerun after stratification according to the presence or absence of cognitive impairment. RESULTS: Four hundred twenty-one individuals (7%) met frailty criteria. Cognitive impairment was present in 10%, 12%, and 22% of the nonfrail, prefrail, and frail subjects, respectively. Those classified as frail scored lower on the MMSE and IST than those classified as prefrail and nonfrail. After adjustment, frail persons with cognitive impairment were significantly more likely to develop disability in activities of daily living (ADLs) and instrumental ADLs over the following 4 years. The risk of incident mobility disability and hospitalization was marginally greater. Incident dementia was greater in the groups with cognitive impairment irrespective of their frailty status. Conversely, frailty was not a significant predictor of mortality. CONCLUSION: Cognitive impairment improves the predictive validity of the operational definition of frailty, because it increases the risk of adverse health outcomes in this particular subgroup of the elderly population.